Gadd45a Functions as a Promoter or Suppressor of Breast Cancer Dependent on the Oncogenic Stress - Tront, Jennifer S. (2010)
Gadd45a plays a pivotal role as a stress sensor that modulates cellular responses to various stress stimuli, including oncogenic stress. We reported that the stress sensor Gadd45a gene functions as a tumor suppressor in Ras-driven breast tumorigenesis via increasing JNK-mediated apoptosis and p38-mediated senescence. In contrast, here, we show that Gadd45a promotes Myc-driven breast cancer by negatively regulating MMP10 via GSK3 β/β-catenin signaling, resulting in increased tumor vascularization and growth. These novel findings indicate that Gadd45a function as either tumor promoter or suppressor is dependent on the oncogenic stress and is mediated via distinct signaling pathways. Collectively, these novel findings highlight the significance of the type of oncogenic alteration on how stress response genes function during initiation and progression of tumorigenesis. Since gadd45a is a target for BRCA1 and p53, these finding have implications regarding BRCA1/p53 tumor suppressor functions.